Spheroid‐based 3D cell cultures identify salinomycin as a promising drug for the treatment of chondrosarcoma. Issue 8 (14th March 2018) - Perut, Francesca; Sbrana, Francesca V.; Avnet, Sofia; De Milito, Angelo; Baldini, Nicola
ABSTRACT: Chondrosarcoma (CS) is a cartilage malignancy of adulthood that is treated by surgery alone, since chemotherapy is considered ineffective. Unfortunately, a large proportion of patients with CS develop lung metastases, and several die of the disease. In this study, we compared 3D‐spheroid cultures and conventional cell monolayer models in order to identify the best way to select anticancer agents that could be effective for the systemic control of CS. Using SW1353 cells, we developed a three‐dimensional (3D) in vitro culture model to mimic in vivo features of CS microenvironment and evaluated the efficacy of different drugs to modulate CS cell proliferation and survival in 2D versus 3D‐cultures. Doxorubicin (DXR) and cisplatin, that are widely employed in sarcomas, were less effective on 3D‐CS spheroids when compared to standard monolayer models, whereas treatment with the ionophore salinomycin (SAL) had a strong cytotoxic effect both on 2D and 3D‐cultures. Furthermore, as demonstrated by the reduced viability and the enhanced DXR nuclear localization, SAL enhanced DXR cytotoxicity in 3D‐CS spheroids also at sub‐lethal doses. SAL activity on 3D‐CS spheroids was mediated by a significant induction of apoptosis via caspase activation. This study demonstrates that preclinical tests significantly differ in monolayer and 3D cultures of CS cells. Using this approach, SAL, alone or, at sub‐lethal concentrations, in combination with DXR, represents a promising agent for the systemic treatment of CS. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2305–2312, 2018.